Promotional cultures the rise and spread of advertising, public relations, marketing and branding - Davis, Aeron (Polity, 2013)
In the twenty-first century, promotion is everywhere and everything has become promotable: everyday goods and organizations, people and ideas, cultures and futures. This engaging book looks at the rise of advertising, public relations, branding, marketing and lobbying, and explores where our promotional times have taken us.